Synthesis and crystal structure of 1-{4-[(3-bromo-2-hydroxy-benzylidene)amino]phenyl}ethanone, C15H12BrNO2 - Jin Yi; Fu Tao; Ma Bo-Yang; Wei Ping; Zhao Ji-Xing; Zhao Li (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C15H12BrNO2, monoclinic, P21/c (no. 14), a = 11.7848(3) Å, b = 10.0857(3) Å, c = 12.2695(4) Å, β = 111.2020(10)°, Z = 4, V = 1359.61(7) Å3, Rgt(F) = 0.0306, wRref(F2) = 0.0745, T = 173(2) K.